2008
DOI: 10.1530/rep-08-0289
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of glucocorticoids by 11β-hydroxysteroid dehydrogenase enzymes increases during the meiotic maturation of porcine oocytes

Abstract: Recent reports have shown that glucocorticoids can modulate oocyte maturation in both teleost fish and mammals. Within potential target cells, the actions of physiological glucocorticoids are modulated by 11b-hydroxysteroid dehydrogenase (HSD11B) isoenzymes that catalyse the interconversion of cortisol and cortisone. Hence, the objective of this study was to establish whether HSD11B enzymes mediate cortisol-cortisone metabolism in porcine oocytes and, if so, whether the rate of glucocorticoid metabolism change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
0
12
1
Order By: Relevance
“…In mammals, high levels of free glucocorticoids are present in the ovarian follicle antral fluid and glucocorticoid receptors (GRs) are present in ovarian tissues [5][6][7][8][9][10][11][12], suggesting an essential role for the glucocorticoid in oocyte development and maturation, possibly by modulating the meiotic competence of the oocyte [7]. Elevated ovarian glucocorticoids were found to have adverse affects on the maturation of oocytes and increased anovulation [13][14][15][16][17], but it is not clear whether these responses can be attributed to a direct action of the glucocorticoids on ovarian steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, high levels of free glucocorticoids are present in the ovarian follicle antral fluid and glucocorticoid receptors (GRs) are present in ovarian tissues [5][6][7][8][9][10][11][12], suggesting an essential role for the glucocorticoid in oocyte development and maturation, possibly by modulating the meiotic competence of the oocyte [7]. Elevated ovarian glucocorticoids were found to have adverse affects on the maturation of oocytes and increased anovulation [13][14][15][16][17], but it is not clear whether these responses can be attributed to a direct action of the glucocorticoids on ovarian steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, if the oocytes and early embryos are unable to metabolize cortisol, embryogenesis may be compromised (Leatherland et al 2010. The antral fluid of the ovarian follicles in mammals contains relatively high concentrations of unconjugated cortisol, the levels of which are regulated within narrow limits by the actions of two forms of 11b-hydroxysteroid dehydrogenase (11b-HSD) that are co-expressed in the mural granulosa cells (Michael et al 2003, Sunak et al 2007, Michael & Papageorghiou 2008, Webb et al 2008. The maintenance of a stable high concentration of cortisol suggests that the glucocorticoid plays an important role in the 'normal' development and maturation of the oocyte.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that primarily the HSD11B enzyme system acts within porcine oocytes, converting cortisol to cortisone, and this enzymatic inactivation increases during oocyte maturation [48]. This HSD11B activity may also have limited the potentially harmful effect of physiological levels of cortisol in the oocyte in the present work.…”
Section: Discussionmentioning
confidence: 69%